Metode Penguatan Pendidikan Akhlak - Moh Ulul Azmi (Universitas Islam Tribakti Lirboyo Kediri, 2023)
This research aims to understand the methods for strengthening moral education at the Majelis Taklim Padepokan Arrohman Loringpasar and the implications of these methods for the congregation of Majelis Taklim Arrohman Loringpasar. Consequently, the researcher will provide a description and analysis. This research employs a qualitative approach and falls under the category of field research. In this study, data collection methods such as observation, interviews, and documentation are used. Data is obtained from the caregivers, administrators, and congregation members of Majelis Taklim Arrohman Loringpasar. The results of this research reveal that there are various forms of activities intended to strengthen moral values within Majelis Taklim Arrohman Loringpasar. Some of these activities include the study of Islamic classical texts, spiritual exercises, and martial arts. The implications of these diverse activities concerning moral development include the emergence of role models and processes of spiritual purification, illumination, and manifestation within the congregation members.The methods employed have a positive impact on shaping virtuous character among the congregation. When the caregivers demonstrate exemplary behavior and morals, the congregation members feel inspired and motivated to follow their example. Additionally, the processes of spiritual purification, illumination, and manifestation within the congregation contribute to the development and strengthening of moral values in their relationship with God, fellow humans, and the universe.